Estudio del sector industrial de palta hass para consumo nacional - Granda Toro, Renzo (2021)
Currently, avocado’s consumption in has been growing, which generates a greater production at the national level (MINAGRI, 2019). Many types of avocado are produced in Peru, including the hass avocado. The hass avocado is smaller in size than the strong avocado, but its quality, flavor and shelf life is higher. It is grown mainly on the coast of Peru, highlighting the departments of La Libertad and Lima. For cultivation, the climate required is not to be icy. In addition, a place should be found where floods or stagnations cannot occur, since excessive humidity can kill the crop (Palpex, 2011). The study seeks to know the national Hass avocado market, the variables that compose it and its development. For this, the main actors of the hass avocado industrial sector can be identified in order to analyze the competition; determine the competitive advantages in the national market of hass avocado; and analyze the technology used in the hass avocado market, the environment, the economic and social environment that this product faces.